Efficient emerging contaminants (EM) decomposition via peroxymonosulfate (PMS) activation by Co3O4/carbonized polyaniline (CPANI) composite: Characterization of tetracycline (TC) degradation property and application for the remediation of EM-polluted wate - Jin Qian; Xiaohui Mi; Zhijie Chen; Weihang Xu; Liu, Wen; Rui Ma; Yichu Zhang; Yufei Du; Bing-Jie Ni (Journal of Cleaner Production, 2023)
Earth abundant transition metal-based materials are widely served as peroxymonosulfate (PMS) activators for degradation of emerging contaminants. However, the agglomeration of catalyst particles and metal ion leaching hinder their practical applications for pollutant decomposition. In this study, a Co3O4-carbonized polyaniline composite (Co3O4/CPANI) was implemented for PMS activation. The Co3O4/CPANI + PMS system exhibited high catalytic performance toward tetracycline (TC) degradation (degradation efficiency of 92.11%, initial TC level of 20 mg/L). Moreover, the practical application potential of Co3O4/CPANI + PMS system was well verified with three antibiotics (i.e., TC, doxycycline (DOX), and ciprofloxacin (CIP)) at highest actual aquatic environmental levels (1.0 and 0.5 mg/L). In the established Co3O4/CPANI + PMS system, both radicals (•O2−, •OH and SO4•-) and non-radical (1O2) contributed to TC degradation, and 1O2 was the dominant reactive oxygen species (ROS). CO groups, oxygen vacancies (OVS), redox pairs of Co2+/Co3+ species, and graphitic N all served as active sites in the PMS activation process, especially, OVS were crucial for the generation of 1O2. This study provides an efficient method for the synthesis of metal-based nanocatalysts with low nanoparticle aggregation and metal leaching which could act as a sustainable PMS activator for the remediation of TC-polluted water environment.
Keywords: Advanced oxidation processes; CoO/carbonized polyaniline (CPANI) composite catalysts; Emerging contaminants; PMS activation; Radicals and non-radicals